Single-cell analysis in endometrial research. Issue 4 (29th November 2022) - Cao, Dan-Dan; Wang, Jue; Yao, Yuan-Qing; Yeung, William Shu-Biu
Abstract : Human endometrium undergoes dynamic shedding, regeneration, and differentiation, with remarkable changes in gene expression across the menstrual cycle. The development of a receptive endometrium within a particular time frame (window of implantation) is critical for successful embryo implantation. To understand the role of the endometrium in human fertility and regenerative biology, transcriptomic characterization of the endometrium has traditionally been pursued at the tissue bulk level using microarray and next-generation sequencing. Owing to the rapid development of single-cell RNA sequencing technology, researchers have uncovered heterogeneous molecular activities in individual cells masked by bulk analysis. In this review, we opted to mainly focus on single-cell analysis in endometrial research and introduce basic knowledge of single-cell RNA sequencing and the isolation of single cells from endometrial cells. We also discussed how single-cell approaches are used to understand the transformation and regeneration of the endometrium physiologically and uncover endometrial factors that contribute to uterine pathology.